Propranolol in Use for Treatment of Complex Infant Hemangiomas: Literature Review Regarding Current Guidelines for Preassessment and Standards of Care before Initiation of Therapy - Andreas Fette (The Scientific World Journal)
In 2008, the positive effects of propranolol on infantile hemangiomas (IH) have been discovered serendipitously by Léauté-Labrèze and her coworkers. Since then, propranolol has been in use in allday clinical practice worldwide for treatment of IH. It even caused some kind of paradigm shift in the overall management of these lesions, though propranolol is still not FDA approved, respectively, in “off-label” use for this indication in the majority of institutions. Thus, the aim of this communication is to evaluate the literature for current evidence regarding guidelines for preassessment and standards of care before initiation of therapy.